The role of the developmental state in Northern Ethiopia’s Raya Valley Groundwater Irrigation Project: an institutional economics perspective - Shumuye, Muleta Yirga (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.